Efficient charged particle propagation methods. Issue 1 (1st February 2023) - Reichherzer, P.; Becker Tjus, J.
Abstract: In astrophysics, the search for sources of the highest-energy cosmic rays continues. For further progress, not only ever better observatories but also ever more realistic numerical simulations are needed. We compare different approaches for numerical test simulations of ultra-high-energy cosmic rays in the intergalactic magnetic field and show that all methods provide correct statistical propagation characteristics of the particles in means of their diffusive behaviour. Through convergence tests, we show that the necessary requirements for the methods differ and ultimately reveal significant differences in the required simulation time.